1990
DOI: 10.1093/nar/18.15.4361
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the expression of the human HOX-5.1 gene

Abstract: The complex mechanisms underlying homeobox genes expression involve regulation at transcriptional, post-transcriptional and translational levels. The multiple transcripts of the human HOX-5.1 gene are expressed differentially in tissue- and stage-specific patterns during embryogenesis, and differentially induced by retinoic acid (RA) in human embryonal carcinoma (EC) NT2/D1 cells. We have sequenced 6.3 Kb of the genomic region containing the HOX-5.1 gene and analyzed its mechanisms of expression. Two alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Nevertheless, it is quite clear that a large subset of them share some unusual features. They are often multiple, sometimes close together, sometimes spaced up to several kilobases apart (7,8,33). A relatively high proportion contain minimal promoters that do not have TATA boxes but have initiators instead.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is quite clear that a large subset of them share some unusual features. They are often multiple, sometimes close together, sometimes spaced up to several kilobases apart (7,8,33). A relatively high proportion contain minimal promoters that do not have TATA boxes but have initiators instead.…”
Section: Discussionmentioning
confidence: 99%
“…NTera-2 cells were maintained in their undifferentiated phenotype by continuous growth at high cell density (5-50 ϫ 10 6 cells/175 cm 2 flask), and differentiation was induced by seeding cells at 2 ϫ 10 6 cells per 175-cm 2 flasks in 10 Ϫ6 M retinoic acid (Sigma) as described (28). P19 cells were grown in ␣-modified minimal essential medium (Invitrogen) containing 7.5% heat-inactivated newborn calf serum (Invitrogen) and 2.5% fetal bovine serum (Invitrogen) and split 20 times every other day using 0.05% trypsin-0.02% EDTA as previously described (29).…”
Section: Methodsmentioning
confidence: 99%
“…97,98,100 Several mechanisms have been identified that regulate expression of HOX genes. The identification of TAAT sequences and retinoic acid response elements in upstream regions allows the binding and activation or repression by homeoproteins [101][102][103][104][105][106] (autoregulation) and activation of expression by retinoic acid. [107][108][109][110][111][112][113][114][115][116] Early HOX gene expression in Drosophila is dependent on segmentation genes of the pairrule (activators) and gap (repressor) families.…”
Section: Hox Gene Expressionmentioning
confidence: 99%